(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This study employs digital text analysis to explore Jadid publications and their role in transforming media discourse in Central Asia. Utilizing a corpus of digitized texts – including newspapers, periodicals, and archival documents produced by Jadid reformers – this research examines linguistic patterns, thematic trends, and discursive shifts that accompanied the modernization efforts of the Jadid movement. By applying corpus linguistics tools such as frequency, collocation, and concordance analyses, the study provides quantitative and qualitative insights into how Jadid publications contributed to cultural and media transformations.